China in Soviet Opera: Sergei Vasilenko’s Son of the Sun and Its Stage Fate - Yulia P. Medvedeva (Современные проблемы музыкознания)
The attitude of the general public and musical circles to the work of Sergei Nikiforovich Vasilenko (1872–1956) changed more than once. Now that it becomes possible to consider his work more objectively, it is attracting the increasing attention of performers and researchers. One of Vasilenko’s most interesting works yet to receive critical reappraisal is his opera Son of the Sun [Sïn Solntsa] (1929). A year after its premiere at the Bolshoi Theatre, the opera was largely forgotten; however, as the present work sets out to demonstrate, this was primarily as a result of political and not artistic factors. Up until now, Son of the Sun has not been the object of detailed musicological analysis. Fortunately, the score, archival materials and critical responses to the production have been preserved. By turning to them, one can reconstruct the atmosphere of its creation to provide this important work with an unbiased assessment and answer the question about the reasons for its unhappy stage fate. The relevance of Son of the Sun today is determined by another circumstance: it is the only Soviet opera whose subject matter is connected with China: the libretto by Mikhail Galperin is based on the events of the Boxer Rebellion of 1899–1901. As well as drawing on elements of romanticism, impressionism, and modernism, Vasilenko’s music reveals a keen interest in Chinese folklore: in addition to repeatedly quoting themes from Chinese folk music, the composer finds new ways of working with them that correspond to the nature of the material itself. In the musical dramaturgy of the opera, four independent lines can be distinguished: ethnographic, lyrical, revolutionary–ideological and “topical”. In the last of them, the composer comes close to the genre of Zeitoper, which became popular in European musical theatre during the 1920s and 1930s. The study of Vasilenko’s forgotten opera on the eve of its 100th anniversary shows that Son of the Sun has many merits that justify its more thorough study and new attempts to bring it to stage.